The Extraordinary Solution for Indonesia Economic Crisis: Shariah Capital Market - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
l11e historical development of the Islamic finance industry which includes banking, insurance and capital markets is fundamentilly a very long historical process. l11e Islamic Shari.a principles applied in the banking industry and Cairo is a country founded the first Islamic bank around 1971 under the name